A cytosolic thiouridylase gene MoCTU2 in Magnaporthe oryzae is important for vegetative hyphal growth, conidiation, and responses to rapamycin and high temperature. (September 2022) - Yan, Han; Zuo, Yushan; Zhang, Huixia; Liu, Cuicui; Yang, Jun; Chen, Lijie
Abstract: Cytoplasmic thiouridylase Ctu1-Ctu2 protein complex is responsible for thiolation on the wobble base U34 of tRNAs and plays an important role in cell development in model organisms. However, the biological function of this protein complex in plant pathogenic fungi remains unknown. In this study, we identified a cytosolic thiouridylase gene MoCTU2 in the rice blast fungus Magnaporthe oryzae . The Δ Moctu2 mutant showed reduced vegetative hyphal growth and conidiation, and increased responses to rapamycin and high temperature. However, MoCTU2 had a minor impact on the ability of the mutant causing blast disease on rice. MoCTU2 was constitutively expressed at various developmental stages, with a peak during appressorium formation; the MoCtu2-GFP fusion was evenly distributed in the cytoplasm. Altogether, our findings indicate that the cytosolic thiouridylase gene MoCTU2 is required for fungal development, conidiation, and responses to rapamycin and high temperature in the blast fungus. Highlights: MoCTU2 is important to vegetative hyphal growth and conidiation. MoCTU2 is required for the sensitivity to rapamycin and high temperature. MoCtu2 is localized into the cytoplasm and highly expressed in the appressorium.